Innovation in application of Hiyal (legal device) on Ijarah based contract in Malaysia / Mohd Ashrof Zaki Yaakob … [et al.] - Yaakob, Mohd Ashrof Zaki; Osman, Muhamad Rahimi; Khalid, Mohammad Mahyuddin; Mohd Sirajuddin, Mohd Dasuqkhi; Yakob, Asmadi (Research Innovation Business Unit, 2014)
This study examines the concept of hiyal (legal device) in islamic financial contract with special reference to ijarah based contract. The context of this study is the nascent islamic finance industry in which these hiyal play a leading role, especially in various instrument offered by islamic financial institutions. The majority of juristic trends are seen to categories hiyal into permissible and impermissible types. Furthermore, islamic financial institutions is developed on hybrid contract while shariah prohibits the combination of contracts (bayatayn fi bayah).thus, it is important to investigate the application of hiyal in islamic financial institution as people do not realize the way it should be. Scope and limitation of this study focuses on ijarah based contract in islamic financial institutions. The term hiyal is the plural of hilah, which can be described as artifice, device, expedient, stratagem, the means of evading a thing, or effecting an object (the encyclopedia of islam online, 2012) (aishath muneeza, 2011). Technically it may be described as the use of legal means for extra-legal ends that could not be achieved directly with the means provided by the shariah (muhammad tahir mansoori, 2011) (mohamed fairooz abdul khir, 2011). But, there are polemics among scholars in permitting hiyal as a legal device, and they categorise hiyal into permissible and impermissible types. Meanwhile, ijarah is the most incorporated instruments in islamic financial institution. In general, there are six instruments of ijarah based contract, namely: 1. Ijarah financing, 2. Al-ijarah thumma al-bay (aitab) (islamic hire purchase), 3. Musharakah munataqisah (diminishing partnership), 4. Sukuk al-ijarah, 5. Ijarah mawsufah fi al-dhimmah, 6. Ijarah mudafah ila al-mustaqbal. Shariah legitimacy of islamic banking has been a subject of intense debate and controversy among the scholars. A group of scholars holds the opinion that current islamic banking practices are not islamic in real sense (muhammad tahir mansoori, 2011). A major objection raised is that islamic banking heavily relies on hiyal i.e. certain stratagems and subterfuges to circumvent certain shariah prohibitions especially those on riba. These scholars contend that murabaha and ijarah are merely hiyal not real islamic alternatives to conventional banking (muhammad tahir mansoori, 2011). On 29th august 2008, a fatwa was issued by the scholars belonging to prominent religious seminaries of pakistan in which they declared the present islamic banking un-islamic. Their main objection is that it is primarily structured on hiyal that frustrate higher purposes of shariah. The products developed by the banks may conform to the letter of islamic law, but frustrate the spirit and purpose of law (muhammad tahir mansoori, 2011). For example, the contract of al-ijarah thumma albaya which known as an islamic hire purchase. The hiyal committed in this transaction is due to the fact that whole purpose of the contract is not to lease, however is to sell the product at the end of the tenure. Thus, the hiyal part is evident when the customer defaults in the payment of the rent and when he is forced to buy the subject matter for the price stipulated by the bank. This shows that the real intention behind the whole ijarah facility is to give a loan to the customer and word ijarah is used as a sham (aishath muneeza, 2011). The purpose of this study was to examine whether the islamic financial products and banking transactions are in the nature of stratagems that frustrate the purpose and spirit of shariah or they are only clever answers to difficult problems, commonly known in islamic jurisprudence as makharij (a way out without frustrating the spirit and purpose of shariah)